Association of Lung CT-scans and Laboratory Findings with Disease Outcomes in COVID-19 Patients - Sahar Ravanshad; Marieh Alizadeh; Aida Bakhshi; Sepideh Hejazi; Mina AkbariRad; Hassan Mehrad-Majd (Reviews in Clinical Medicine)
Introduction: The COVID-19 pandemic has underscored the necessity of investigating the relationship between radiological and laboratory findings with disease outcome in COVID-19 patients. This study aimed to explore the association between CT-scan finding and laboratory results with disease outcome, including recovery without complications, ICU admission, or mortality.Methods: This retrospective cross-sectional study analyzed medical records and laboratory data from COVID-19 patients at our institution from September 2020 onwards. All demographic, laboratory findings, as well as CT-scan data such as ground-glass opacity, consolidation, pleural effusion, cardiomegaly, mediastinal lymphadenopathy, and pulmonary involvement score at admission were collected. Patients were categorized based on outcome status and compared for all study variables. Results: Significance differences were observed for CT-score values between deceased patients and those who recovered (P<0.001), indicating a more severe lung changes in patients who died due to COVID-19. Additionally ICU-admitted patients had higher likelihood of underlying comorbidities and elevated CT-score levels. Laboratory markers such as ESR, Ferritin, LDH, Neutrophil count, and RDW were significantly higher in patients requiring ICU admission (P<0.05). Deceased patients were more likely to have underlying diseases, ground glass opacity, cardiomegaly, and higher CT-scores. Laboratory markers such as ESR, CRP, Ferritin, LDH, and others were also significantly higher in expired patients.Conclusion: There was a strong association between laboratory and CT-scan findings with disease outcomes in COVID-19 patients. The combination of laboratory markers and CT-scan findings can serve as robust predictors of disease outcomes. Further studies are needed to validate these findings in larger cohorts.